2003
DOI: 10.1021/ed080p1084
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Chemistry Course as a Means To Foster Freshmen Learning

Abstract: Simulations, graphing, and microcomputer-based laboratories have been used in the last two decades as effective teaching methods in science education at both college and high school levels (1-5). Scientists, engineers, and science educators use models to concretize, simplify, and clarify abstract concepts, as well as to develop and explain theories, phenomena, and rules. Researchers underscored the need for models as enablers of students' mental transformation from two-dimensional to three-dimensional represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 29 publications
5
46
0
5
Order By: Relevance
“…Providing the technology that has the capability to support high levels of interaction does not always guarantee that substantive discussion and collaboration will occur (Clark, 1994;Salomon & Perkins, 1998). However, this study has shown that when well-designed educational technology is intertwined with social constructivism, improvement in both the cognitive and affective domains can be achieved not only for middle and high school science education, as shown in previous studies Dori & Barak, 2001;Linn, 1998), but also in undergraduate science education (Dori, Barak & Adir, 2003) in general and physics education in particular .…”
Section: Discussion and Further Researchmentioning
confidence: 63%
See 1 more Smart Citation
“…Providing the technology that has the capability to support high levels of interaction does not always guarantee that substantive discussion and collaboration will occur (Clark, 1994;Salomon & Perkins, 1998). However, this study has shown that when well-designed educational technology is intertwined with social constructivism, improvement in both the cognitive and affective domains can be achieved not only for middle and high school science education, as shown in previous studies Dori & Barak, 2001;Linn, 1998), but also in undergraduate science education (Dori, Barak & Adir, 2003) in general and physics education in particular .…”
Section: Discussion and Further Researchmentioning
confidence: 63%
“…action does not always guarantee that substantive discussion and collaboration will occur (Clark, 1994;Salomon & Perkins, 1998 (Clark, 1994;Salomon & Perkins, 1998 1998), but also in undergraduate science education (Dori, Barak & Adir, 2003) in general and physics education in particular . The practice of constructivism in science education…”
Section: Discussion and Further Researchmentioning
confidence: 99%
“…Viaceré štúdie ukazujú, že jedným z úspešných spôsobov, ako zvýšiť motiváciu žiakov k štúdiu prírodovedných predmetov je pomocou integrácie vizualizácie a animácie do vyučovacieho procesu (Barak -Dori 2005;Barak et al 2011). Aplikácia animácií a vizualizácie prispieva študentom ku konceptuálnemu porozumeniu (Barak, Dori 2005), k úspechu v učení (Dori et al 2003,. Dori -Belcher 2005, k priestorovej orientácii (Barnea -Dori, 2000) a motivácii k učeniu sa vedeckých poznatkov (Barak et al, 2011).…”
Section: úVodunclassified
“…This is sometimes referred to as "near-distance" or "hybrid distance" courses (Roberts & Dyer 2005b;Chen et al 2010). Web lectures come in many forms and are sometimes referred to as lectures on the web or multimedia lectures (Dori et al 2003;Rafaeli et al 2004;Ketterl et al 2009). They usually consist of a combination of video, audio, and presentation slides (e.g., PowerPoint) streamed over the web (Day 2008).…”
Section: An Online Teaching and Learning Strategymentioning
confidence: 99%